Long Acting Reversible Contraceptive Uptake in a Student Health Center Following the 2016 Presidential Election [9E]. (May 2018) - Sridhar, Aparna; Baker, Zoe; Elias, Sam
Abstract : INTRODUCTION: In the context of recent political changes and concerns regarding the potential repeal of mandated contraception coverage in the United States (U.S.), the media reported a sudden increased interest in long acting reversible contraceptives (LARCs), such as intrauterine devices (IUDs) and etonogestrel implants (Nexplanon). Data compiled from 2500 Aetna Health physicians similarly revealed an abrupt increase in IUD-related appointments from October-December 2016. METHODS: This is a retrospective review of medical records, comparing the number of women presenting for LARC insertions at the UCLA Arthur Ashe Student Health Center in Los Angeles in the 8 weeks preceding and following the 2016 U.S. presidential election. The volume of LARC insertions during this timeframe was also compared to the volume of LARC insertions during the same 16-week period in the previous year. RESULTS: The total number of LARCs inserted increased from 53 in the eight weeks prior to the 2016 presidential election, to 118 in the eight weeks after the election, representing a 123% increase in LARC uptake (p-value=0.02). Over the same 16-week period in the previous year, there was no statistically significant change in number of LARC procedures. No other major changes occurred in the clinic over the 8-week period after the election to account for an increased volume of LARC insertions. CONCLUSION: LARC intake increased significantly in our patient population following the 2016 presidential election. We will continue to monitor LARC uptake patterns to determine whether an increased volume of LARC insertions is sustained over a larger timeframe.